Association of Serum Folate and Troponin-I Levels in Acute Myocardial Infarction among Type 2 Diabetic Patients - Islam, Rumana; Mishu, Farzana Akonzee; Hasan, Sayed Rakib; Tabassum, Mariya; Afroz, Tamanna; Al Imran, Md Rakib; Alam, Mohammad Ashraful (International Journal of Human and Health Sciences (IJHHS), 2026)
Acute myocardial infarction (AMI) is a major cause of death and loss of quality of life worldwide. Folate deficiency is an emerging risk factor for AMI. This case-control study was conducted in the Department of Biochemistry and Molecular Biology of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) Hospital, Dhaka, Bangladesh, between July 2021 and June 2022, to determine the possible correlation between serum folate and troponin-I levels in acute myocardial infarction among type 2 diabetic patients. A total 80 type 2 diabetes mellitus (DM) patients were included in the study: 40 patients with acute myocardial infarction (AMI) were in group-I (case) and 40 patients without AMI were in group-II (control). We adopted a convenient sampling technique. After 8-12 hours fasting blood specimens were collected from study participants to estimate serum troponin-I, folate, fasting blood glucose and HbA1C levels. Serum folate level was significantly lower in group-I compared to group-II (3.87±3.17ng/ ml vs. 8.19±3.07ng/ml; P<0.01), while serum troponin-I level was significantly higher in group-I than that of group-II (3035.82±728.16pc/ml vs. 7.58±3.19pc/ml; P<0.01). Regarding glycaemic status, fasting blood glucose (FBG) level was found significantly higher in group-I than that of group-II (10.17±3.56mmol/L vs. 8.64±2.28mmol/L; P<0.01), while HbA1C was also observed significantly higher in group-I compared to group-II (9.81±4.28% vs. 8.45±1.92%; P<0.01). A significant negative correlation was found between serum folate and troponin-I level (r=–0.301; P<0.01). Multiple logistic regression also showed a significant negative association of folate with troponin-I level (P<0.001) To conclude, serum folate level is decreased in AMI in diabetic patients compared to diabetic patients without AMI. Therefore, early detection of serum folate level helps to prevent of AMI and its recurrence in Type 2 diabetic patients. International Journal of Human and Health Sciences Vol. 10 No. 01 Jan’26 Page: 48-52